A Case Study on Ayurvedic Management of Ovarian Endometrioma (International Journal of Ayurveda and Pharma Research, 2021)
Menstruation is purely a natural process occurring in a woman’s body each month. It is the visible manifestation of cyclic uterine bleeding due to shedding of endometrium. Endometriosis is a common health problem for women. It is the occurrence of benign ectopic endometrial tissues outside the uterus. Ovarian endometrioma is the most common form of endometriosis. It increases the risk of ovarian cancer in reproductive age group among woman. Although most of the endometriomas are benign, some of them may undergo malignant changes. This is the case report of a 38 year old lady who presented with increased menstrual bleeding with excessive clots, dysmenorrhoea, burning micturition, and dyspareunia. On USG she was detected to have bilateral hydrosalpinx and ovarian endometrioma. Based on the clinical features presented by the patient amapachana, kaphapittasamana and vataanulomana mode of management was given. After six months of internal medications symptoms reduced considerably and there was no endometrial cysts and features of hydrosalpinx in USG.